PENGARUH DAYA TARIK WISATA, FASILITAS DAN AKSESIBILITAS TERHADAP KEPUTUSAN BERKUNJUNG DI OBJEK WISATA PANTAI AIR MANIS KOTA PADANG - Mike Kusuma Dewi; Muhammad Rivandi; Elsa Meirina (JURNAL MANAJEMEN UNIVERSITAS BUNG HATTA, 2020)
The purpose of this study was to examine the effect of tourist attraction, facilities and accessibility on the decision to visit the Air Manis Beach Tourism Object in Padang City. Sampling was done by simple random sampling method, the sample in this study were 99 visitors of the city of Padang sweet water beach. The type of data in this study is cross sectional. The data collection technique in this study is the technique of collecting questionnaire methods. The application used to process data in the study was SPSS version 25. The results showed that tourist attraction had a positive influence on visiting decisions, facilities had a positive effect on visiting decisions and accessibility had a positive effect on visiting decisions at Air Manis Beach Tourism Object in Padang. This is evidenced by the results of the t test with a significance level of less than 0,05. For further research, add the number of variables and the amount of data so that the data ismore accurate.